INFLUENCE OF STRESS MANAGEMENT ON BLOOD PROFILE OF BROILER CHICKENS - KUMAR, SANJAY; PRASAD, C. M.; KUMARI, SUSHMA (Indian Journal of Animal Production and Management, 2017)
ABSTRACTA study was conducted to investigate the influence of stress management on bloodprofile of broiler chickens kept under cage system. Two hundred four day old commercialbroiler chicks were randomly selected and divided into four groups equally and giventreatment of different anti stress agents along with standard diet. The blood profile wasinvestigated at 42 day age of five chickens randomly selected from each group. The Hb%,TEC(106/mm3), PCV% ,TLC (103/mm3) and differential counts along with biochemicalparameters viz. Blood sugar (mg/dl), serum protein (g/dl), SGOT and SGPT (IU) indicatedimprovement in general health condition of birds in anti stress treated group than control.The effect was best on zeetress followed by honey, glucose and control group.